Agronomic performance of Arabica coffee cultivars in the subtropical humid environment of Vale do Ribeira Paulista, Brazil1 - Carvalho, Alex Mendonça De [UNESP]; Teramoto, Érico Tadao [UNESP]; Botelho, Cesar Elias; Carvalho, Gladyston Rodrigues; Lima, Amador Eduardo De; Guerreiro, Oliveiro (Universidade Federal de Viçosa, 2023)
This research is related to the evaluation of vegetative growth parameters, initial yield and incidence of pests and diseases of twelve Arabica coffee cultivars submitted to the subtropical humidity environment of Vale do Ribeira Paulista, Brazil. The experiment was performed in the Experimental Campus of the UNESP in Registro, in a randomized block design, with three replications. Stem diameter, number of plagiotropic branches, plant height, number of internodes of plagiotropic branches, length of the first plagiotropic branch, incidence of brown eye spot and phoma leaf spot on coffee leaves, infestation by leaf miner and the yield of cultivars were evaluated. The results obtained allowed to conclude that: i) cultivars Catuaí Amarelo IAC 62, Catuaí Vermelho IAC 99 and Mundo Novo IAC 379-1 were higher than the others, with yield above the national average in 2020 and percentage of flat beans below 10%; ii) all cultivars evaluated showed a similar level of increment of variables that indicate plant growth and reproductive development; iii) the cultivation environment is favorable to infestation by the leaf miner and unfavorable to the incidence of rust; iv) The prevailing climatic conditions in the Vale do Ribeira Paulista is suitable for the production of Arabica coffee.
Keywords: Coffea arabica; plant growth; yield; Leucoptera coffeella